Caracterização dos indivíduos com dor cervical crônica e eficácia da terapia por fotobiomodulação e estimulação elétrica nervosa transcutânea - Rampazo da Silva, Érika Patrícia (2022)
Non-specific chronic neck pain is a common musculoskeletal disorder that is associated with functional disability and decrease of quality of life. Hence, it becomes relevant that studies are carried out in order to deepen the knowledge of this dysfunction, such as central sensitization and psychosocial factors and to investigate the effectiveness of electrophysical agents as treatment. Therefore, it was performed an observational study with the objective of verifying the presence of central sensitization, psychosocial factors, and range of motion between individuals with non-specific chronic neck pain and healthy control. In addition, another objective was to verify if there is a correlation between pain intensity, neck disability and psychosocial factors in individuals with neck pain. Thirty individuals with chronic neck pain and 30 healthy controls were included. Outcomes: central sensitization (pressure pain threshold, temporal summation and conditioned pain modulation), psychosocial factors (depressive symptoms, pain catastrophizing, and quality of life), and active cervical range of motion. Individuals with neck pain had lower local pressure pain threshold, a decrease in conditioned pain modulation, more depressive symptoms, greater pain catastrophizing, lower quality of life and reduced range of motion for neck rotation when compared to healthy controls (p < 0,05). In addition, moderate correlations were observed between pain intensity, neck disability and psychosocial factors. A randomized clinical trial was performed with the objective of investigating the efficacy of photobiomodulation (PBM) and transcutaneous electrical nerve stimulation (TENS) to relieve pain, both isolated and combined in individuals with neck pain. 144 non-specific chronic neck pain individuals were randomized in 4 groups: PBM+TENS, PBM, TENS e Placebo. First, the individuals were treated with PBM (active or placebo), and then, TENS (active or placebo) during 10 sessions (5x/week). Primary outcome: pain intensity at rest after 10 sessions of treatment. Secondary outcomes: central sensitization, range of motion, psychosocial factors, medications intake and global perceived effect. Outcome measures were collected before and after treatment (10 sessions). Pain intensity and global perceived effect were also evaluated in the follow-up of one month after the end of the treatment. In conclusion, there was no significant difference between groups regarding pain intensity at rest. However, PBM+TENS improved pain intensity during movement, local hyperalgesia, and global perceived effect compared to PBM and placebo. Isolated TENS reduced local and distant hyperalgesia.